Persistence of psychological distress and correlated factors among patients with head and neck cancer. Issue 1 (19th June 2015) - Ichikura, Kanako; Yamashita, Aya; Sugimoto, Taro; Kishimoto, Seiji; Matsushima, Eisuke
ABSTRACT: Objective: Many patients with head and neck cancer (HNC) suffer from psychological distress associated with dysfunction and/or disfigurement. Our aim was to evaluate the ratio of patients with persistence of psychological distress during hospitalization and identify the predictors of persistence or change in psychological distress among HNC patients. Method: We conducted a single-center longitudinal study with self-completed questionnaires. We evaluated psychological distress (the Hospital Anxiety and Depression Scale; HADS) and functional level (the Functional Assessment of Cancer Therapy–Head and Neck Scale; FACT–H&N) among patients during hospitalization at the Medical Hospital of Tokyo Medical and Dental University. Results: Of 160 patients, 117 (73.1%) completed the questionnaire at both admission and discharge. Some 42 (52.5%) patients reported persistent psychological distress. The physical well-being of patients with continued distress was significantly lower than that of other patients (21.7 ± 4.7, 19.4 ± 6.1, 19.5 ± 5.4; p < 0.01), and the emotional well-being of patients with continued distress was significantly lower than that in patients with no distress and reduced distress (22.3 ± 3.5, 20.5 ± 2.5; p < 0.01). Significant of results: Impaired physical and emotional function appears to be associated with persistent psychological distress among HNC patients. Psychological interventions focused on relaxation, cognition, or behavior may be efficacious in preventing such persistent distress.